Effects of tillage on soil nitrogen and its components from rice-wheat fields in subtropical regions of China - Cui, Siyuan; Zhu, Xinkai; Cao, Guangqiao (International Journal of Agricultural and Biological Engineering, 2022)
It is of great significance to explore the effects of different tillage practices on total nitrogen and its components in rice-wheat rotation farmland. The experiment was carried out in Jiangyan County, Jiangsu Province of China, and a total of four treatments were set up: minimum tillage (MT), rotary tillage (RT), conventional tillage (CT), and conventional tillage without straw retention (CT0). The total nitrogen (TN), light fraction nitrogen (LFN), heavy fraction nitrogen (HFN), particulate nitrogen (PN), and mineral-associated nitrogen (MN) in 0-20 cm soil were determined. The results show that MT increased TN concentration by2.26%-27.57% compared with the other treatments in 0-5 cm soil, but it lost this advantage in 5-10 cm and 10-20 cm soil. MT altered the concentration of LFN by 6.03%-95.86%, of HFN by 1.68%-20.75%, of PN by 12.58%-96.83%, and of MN by −1.73%-9.83% as compared to RT, CT, and CT0 in 0-5 cm soil, respectively. With the deepened of soil depth, the concentration of TN, LFN, HFN, PN, and MN decreased quickly in MT, which was lower than that in RT and CT at 10-20 cm soil depth. Straw return increased the concentration of TN and its components in 0-20 cm soil. The concentration of TN was extremely significantly positively correlated with that of LFN, HFN, PN, and MN (p<0.01). The variation of TN was significantly positively correlated with that of LFN, HFN, PN, and MN (p<0.01), and LFN showed the highest sensitivity to tillage practice. In general, minimum tillage combined with straw retention increased the concentration of soil TN and its components in topsoil. LFN was the best indicator to indicate the change in soil total nitrogen affected by tillage practice. Keywords: rice-wheat rotation, soil active nitrogen components, light fraction nitrogen, heavy fraction nitrogen, particulate nitrogen, mineral-associated nitrogen DOI: 10.25165/j.ijabe.20221503.5661 Citation: Cui S Y, Zhu X K, Cao G Q. Effects of tillage on soil nitrogen and its components from rice-wheat fields in subtropical regions of China. Int J Agric & Biol Eng, 2022; 15(3): 146–152.